Samaritans and Saffron Interactive, Samaritans Veterans App: Case Study for the Effective Use of Mobile Learning to Deliver Learning, Development and Wellbeing Management Skills - Sazen, Noorie (International Journal of Advanced Corporate Learning (iJAC), 2022)
This is a case study detailing the 2022 IELA Bronze award winner for Mobile Learning Experience, the Samaritans Veterans App. This project was designed to support military service leavers and veterans in developing wellbeing management techniques and skills in order to facilitate a successful transition back into civilian life.